The effect of raw material selection on physical and mechanical properties of wood plastic composites made from recycled LDPE and wood from invasive trees in South Africa. Issue 2 (4th March 2021) - Acheampong, James B.; de Angelis, Marco; Krause, Andreas; Meincken, Martina
ABSTRACT: WPC boards were produced from recycled low-density polyethylene (rLDPE) and wood from three different invasive species found in the Western Cape, South Africa with the aim of using them as ceiling boards in low-cost housing projects. The study determined differences between two different types of rLDPE and the tree species, as well as tree composition with regards to physical and mechanical board properties. It was found that the difference between using only wood, or the entire tree – with bark, twigs and leaves – as filler in WPC boards is hardly significant. However, the difference between the two sourced recycled plastic was notable.